Planificación Y Preparación Para La Gestión Sustentable De Riesgos Y Crisis En El Turismo Mexicano. Estudio Piloto En Ciudad Juárez, Chihuahua - Manuel Ramón González Herrera; José Manuel Lerma Legarreta (European Scientific Journal, ESJ, 2016)
Tourism is a sector vulnerable to different types of risks and crises caused by multiple and diverse events, which occur in different space-time dimensions. The aim of the paper is to analyze -in Mexican tourism- the planning and preparation process for the sustainable and integrated management of risk and crisis and implementing them through participatory construction of crisis management plan caused by insecurity. A detailed literature review and analysis of regulations was conducted; also interviews with specialists, researchers, academic professionals and managers were developed; case analysis; systematization of secondary data; and group work with three focus groups, developed through a pilot study and in-depth interviews to fill information gaps. As result, the contextualization of the study object and the analysis of the institutional foundations for risk and crisis management is presented; according to such references, the plan for crisis management of tourism in Ciudad Juarez was built in a participatory way. For this purpose, the model of the 4 "R" was used, which is based on the case of crises caused by unsafe situations. It includes a justification, the situation assessment by social perception of the problem, and strategic projection based on the participatory integration of the components of tourism planning.